ANALYSIS OF THE EFFECTIVENESS OF DIGITAL MARKETING: A CASE STUDY OF RAFISA LAMONGAN MSMEs - Riska Apriliyanti; Ali Muhajir; Siti Shoimah (International Journal of Multidisciplinary Reseach, 2026)
The rapid development of digital technology has encouraged micro, small, and medium enterprises (MSMEs) to adopt digital marketing strategies to enhance business competitiveness. This study aims to analyze the effectiveness of digital marketing at Rafisa MSME in Lamongan using the 9P marketing mix framework, including product, price, place, promotion, people, process, physical evidence, partnership, and personalization. A qualitative case study approach was employed involving eight purposively selected informants consisting of the business owner, employees, customers, and business partners. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña with source, technique, and time triangulation. The findings indicate that digital marketing through WhatsApp, Facebook, Instagram, and TikTok has been implemented effectively, with WhatsApp and Facebook serving as the most effective platforms. The implementation of the 9P marketing mix has increased customer acquisition, purchase intention, and customer loyalty. However, challenges remain, including centralized social media management, delayed customer responses, and limited production capacity. The study concludes that digital marketing has positively contributed to Rafisa's business development.